Dichlorido{2-morpholino-N-[1-(2-pyridyl)ethylidene]ethanamine-κ3N,N′,N′′}cadmium - Hisham, N.I.; Gwaram, Nura Suleiman; Khaledi, Hamid; Ali, Hapipah Mohd (International Union of Crystallography, 2010)
In the title compound, [CdCl2(C13H19N3O)], the Cd-II ion is five-coordinate, with the N, N', N ''-tridentate Schiff base ligand 2-morpholino-N-[1-(2-pyridyl) ethylidene] ethanamine and two Cl atoms in a distorted square-pyramidal geometry. In the crystal structure, C-H center dot center dot center dot Cl hydrogen-bonding interactions connect the molecules into a three-dimensional network.